The complete mitochondrial genome of Lasiopodomys brandtii. Issue 1 (2nd January 2020) - Tian, Xiangyu; Gu, Shiming; Pan, Dan; Shi, Luye; Wang, Zhenlong
Abstract: In this study, the complete mitochondrial (mt) genome sequence of Lasiopodomys brandtii was determined using Illumina NovaSeq platform. The assembled genome was 16, 557 bp in length and included 13 protein-coding genes, 2 ribosomal RNA genes, and 22 transfer RNA genes. The total nucleotide composition frequencies present clearly the A-T skew (59.5%), which mostly in D-loop and PCGs regions. Whole mt genome phylogenetic analysis revealed a closely related among Lasiopodomys, Proedromys, and Microtus with high support. It would provide further evolutionary research for the subfamily Arvicolinae.